Analisis penerapan Area Traffic Control System (ATCS) di Pusat Kota Ambon - Hendriks, Petrick Yoshuel; Andani, I Gusti Ayu (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2024)
The Area Traffic Control System is part of the Intelligent Transportation System that coordinates traffic signaling devices according to real conditions in the field so as to have a positive influence on traffic at intersections and the transportation network as a whole. The study was conducted at six intersections that currently use traffic signal devices in Ambon city center. Based on the results of the Analytical Hierarchy Process, it was found that the most influential criterion is road performance with a weight of 58.4% compared to the other two criteria. Of the six intersections, Al-Fatah intersection has the highest total score. However, the total score of the other five intersections is also quite good. The application of this system is more advisable at intersections with good VC ration, spaced with the next intersection and located in commercial activity areas..